(3QHj GdgGOjs - (3GOGf, YGFTIs; (3GdZGfe, MhQs; (3YcGhj, QMGHs; (3cfYGf, CMeOs ((3GdOGQ GdHjVGA, GdeZQHs (3OGQ GdKbGaI ddfTQ hGdJhRjYs, 2024)
(3Ef (B"(3GdgGOj(B" (3jYfj (B"(3GdPj jgOj YHGOg Edi GdWQjb GdUMjM(B". (3CYWGfG QHfG GdYbd dfLO GdWQjb GdUMjM, hNdb cd MjhGf HWQjbI Jecfg ef EjLGO WQjbgs
(3JQHjI OjfjIs
Keywords: (3GdOjfs